Reconstruction of a 1940 Spanish strip cipher by means of a cyclic rotation model applied to encrypted telegrams. Issue 1 (2nd January 2019) - Peinado, Alberto
Abstract: A Spanish strip cipher, known as the "PILAR key", has been reconstructed from a set of encrypted telegrams sent by the General Directorate of Security in Madrid, Spain, to the civil government in Málaga, Spain, in 1940 after the Spanish Civil War. The reconstruction of this unrecorded key is based on the application of a cyclic rotation model to the strip cipher behavior, allowing one to recover the homophone table and the mobile strip. In this way, the messages are correctly deciphered and the PILAR key is now part of the large list of known Spanish strip ciphers.